PENGARUH PENGETAHUAN PERPAJAKAN DAN KEPATUHAN WAJIB PAJAK TERHADAP KEWAJIBAN PENGUSAHA TOKO ALAT BANGUNAN DALAM MELAPORKAN PAJAK PENGHASILAN - Kristisia, Lilianda; dinur, Hairud (Universitas lambung Mangkurat, 2016)
The purpose of study was to examine the effect of tax knowledge (x1) and tax compliance obligations (x2) employers liability store building tool inreporting income tax (Y) in Banjarmasin utara. This research used a quantitative approach. sample taken from shopkeepers building tools in kecamatan Banjarmasin utara. The number of shopkeepers is 44 employer by using sample random sampling. of data collection using questionnaires and data analysis technique that used multiple regression. The result of examination partially the tax knowledge (x1) significant effect on employers store building tool in reporting income tax in Banjarmasin utara the influence 83.0% and tax compliance obligations (X2) of the employer significant effect on store building tool in reporting income tax in kecamatan Banjarmasin utara. It can be concluded there are significant tax knowledge and taxpayer compliance against employers liability tools to store a building in kecamatan Banjarmasin utara partially reported income tax. While simultaneous there are significant tax knowledge and tax compliance knowledge taxpayer substantially influence 94,5%, while 5,5% is the influence of other variables not examined in this study. Regression equation forned is Y= -576 - 0,616(X1) + 0,183(X2) + e.